Fostering participation of general practitioners in integrated health services networks: incentives, barriers, and guidelines - Bergman Howard; Vedel Isabelle; de Stampa Matthieu; Novella Jean-Luc; Lapointe Liette (BMC, 2009)
Abstract Background While the active participation of general practitioners (GPs) in integrated health services networks (IHSNs) plays a critical role in their success, little is known about the incentives and barriers to their actual participation. Methods Data were gathered through semi-structured interviews and a mail survey with GPs enrolled in SIPA (system of integrated care for older persons) at 2 sites in Montreal. A total of 61 GPs completed the questionnaire, from which 22 were randomly selected for the qualitative study, with active and non-active participation in the IHSN. Results The key themes associated with GP participation were clinician characteristics, consequences perceived at the outset, the SIPA implementation process, relationships with the SIPA team and professional consequences. The incentive factors reported were collaborative practices, high rates of elderly and SIPA patients in their clienteles, concerns about SIPA, the selection of frail elderly patients, close relationships with the case manager, the perceived efficacy of SIPA, and improved professional practices. Barriers to GP participation included high expectations, GP recruitment, lack of information on SIPA, difficult relationships with SIPA geriatricians and deterioration of physician-patient relationships. Four profiles of participation were identified: 2 groups of participants active in SIPA and 2 groups of participants not active in SIPA. The active GPs were familiar with collaborative practices, had higher IHSN patient rates, expressed more concerns than expectations, reported satisfactory relationships with case managers and perceived the efficacy of SIPA. Both active and non-active GPs reported quality care in the IHSN and improved professional practice. Conclusion Throughout the implementation process, the participation of GPs in an IHSN depends on numerous professional (clinician characteristics) and organizational factors (GP recruitment, relationships with case managers). Our study provides guiding principles for establishing future integrated models of care. It suggests practical guidelines to support the active participation of GPs in these networks such as physicians with collaborative practices, recruitment of significant number of patients per physicians, the information provided and the accompaniment by geriatricians.